2018
DOI: 10.1016/j.stemcr.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Studies of Missense TREM2 Mutations in Human Stem Cell-Derived Microglia

Abstract: SummaryThe derivation of microglia from human stem cells provides systems for understanding microglial biology and enables functional studies of disease-causing mutations. We describe a robust method for the derivation of human microglia from stem cells, which are phenotypically and functionally comparable with primary microglia. We used stem cell-derived microglia to study the consequences of missense mutations in the microglial-expressed protein triggering receptor expressed on myeloid cells 2 (TREM2), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
181
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(188 citation statements)
references
References 66 publications
7
181
0
Order By: Relevance
“…TREM2 deficiency had no effect on LPS-stimulated TNF and IL-6 secretion, except for TNF release at the highest LPS concentration. This agrees with the two aforementioned studies of T66M and W50C TREM2 mutations, showing that LPS-stimulated inflammation was unaltered (35,39). The R47H mutation did not impair cytokine release induced by LPS alone, but curiously it attenuated IFNγ-primed LPS inflammation, an effect not seen in the TREM2 KO line.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TREM2 deficiency had no effect on LPS-stimulated TNF and IL-6 secretion, except for TNF release at the highest LPS concentration. This agrees with the two aforementioned studies of T66M and W50C TREM2 mutations, showing that LPS-stimulated inflammation was unaltered (35,39). The R47H mutation did not impair cytokine release induced by LPS alone, but curiously it attenuated IFNγ-primed LPS inflammation, an effect not seen in the TREM2 KO line.…”
Section: Discussionsupporting
confidence: 92%
“…and W50C TREM2 lines, phagocytosis of E. coli, zymosan, and acetylated-LDL was unaffected, with the implication that TREM2 is less important in phagocytosis of these cargoes (35,39). Claes et al generated the first published R47H mutation in human embryonic stem cells, and showed that it had no impact on phagocytosis of ex-vivo amyloid plaques or E. coli by microglia-like cells, whereas TREM2 -/+ and -/had defective phagocytosis of these cargoes, agreeing with the current study findings that R47H does not phenocopy TREM2 deficiency in human microglia models (40).…”
Section: Discussionmentioning
confidence: 99%
“…Protocols for the differentiation of iPSCs into microglia have only recently become available, and will undoubtedly be utilized more heavily to examine the effects of AD-linked mutations in the coming years [134][135][136][137][138][139][140]. Induced microglia derived from healthy patients are capable of synaptic pruning, phagocytosis and Aβ uptake, they secrete diverse cytokines and exhibit altered gene expression in response to treatment with exogenous Aβ [134,135].…”
Section: Microgliamentioning
confidence: 99%
“…They will also open the possibility to study CSC developmental hierarchy in tumors and the influence of other cell types or of the environment on CSC fate decisions. While it is possible to incorporate non-neuronal cell types into organoids, such as microglia or other immune cells (Abud et al, 2017;Brownjohn et al, 2018;Ormel et al, 2018;Jacob et al, 2020), the main challenge still remains to recreate an environment that includes the vasculature and other cell types that could exhibit inflammatory and immunitary responses similar to an intact brain (Daviaud et al, 2018;Lancaster, 2018;Mansour et al, 2018).…”
Section: Advantages and Limitations: Which Model To Use?mentioning
confidence: 99%